2017
DOI: 10.1007/s40801-017-0104-y
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Reported Adverse Reactions for Herbal Medicinal Products and Natural Remedies in Sweden 2007–15: Report from the Medical Products Agency

Abstract: BackgroundIn relation to the extensive use of herbal medicinal products in self-care, the safety information is limited and there is a need for improvement. This study describes spontaneously reported adverse reactions related to herbal medicinal products and natural remedies in Sweden.ObjectivesTo evaluate the characteristics and frequency of adverse events recorded by the Swedish Medical Products Agency, where herbal medicinal products and natural remedies were suspected as causative agents.MethodsAdverse dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In addition, many patients who use CAM believe that healing crisis (you get worse before getting better) is a part of the healing process [19]. This together may also be part of the explanation why reported adverse effects from natural remedies are generally low [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many patients who use CAM believe that healing crisis (you get worse before getting better) is a part of the healing process [19]. This together may also be part of the explanation why reported adverse effects from natural remedies are generally low [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a hospital-based observational study in Korea from April 2012 to December 2014, gastro-intestinal system disorders, followed by skin-related disorders were the most common adverse events reported in 163 herbal-drug-associated cases ( 58 ). Likewise in Sweden, the most commonly reported adverse reactions to herbal medicinal products or natural remedies were “skin and subcutaneous tissue disorders” and “gastrointestinal disorders” in a 9-year study on adverse events reported to the Swedish Medical Product Agency ( 59 ). “Skin and hypersensitivity reactions” and “gastrointestinal disorders” had also been reported as the two most common health products related adverse events ( 9 , 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of hepatotoxicity, the event was quickly reversible after discontinuation, except in two cases where liver transplantation became necessary and in one case where the event was fatal [64,69]. Also, when ingested as an HMP, black cohosh (C. racemosa) was associated with five serious reports related to the liver as described by Svedlund et al in their study on spontaneously reported adverse reactions resulting from HMPs and natural remedies in Sweden in the time from 2007 to 2015 [71]. Despite the limited available nonclinical and clinical data, liver toxicity has been also associated with the use of black cohosh by the European Community, as discussed in the assessment report pertinent to the European Community herbal monographs on C. racemosa rhizome [72,73].…”
Section: Latin Namementioning
confidence: 95%